Modulation of Major Human Liver Microsomal Cytochromes P450 by Component Alkaloids of Goldenseal: Time-Dependent Inhibition and Allosteric Effects - McDonald, Matthew G. (Drug Metab Dispos, 2020)
Botanical and other natural products (NPs) are often coconsumed with prescription medications, presenting a risk for cytochrome P450 (P450)-mediated NP-drug interactions. The NP goldenseal (Hydrastis canadensis) has exhibited antimicrobial activities in vitro attributed to isoquinoline alkaloids contained in the plant, primarily berberine, (−)-β-hydrastine, and to a lesser extent, hydrastinine. These alkaloids contain methylenedioxyphenyl rings, structural alerts with potential to inactivate P450s through formation of metabolic intermediate complexes. Time-dependent inhibition experiments were conducted to evaluate their ability to inhibit major P450 activities in human liver microsomes by using a cocktail of isozyme-specific substrate probes. Berberine inhibited CYP2D6 (dextromethorphan O-demethylation; K(I) = 2.7 μM, k(inact) = 0.065 minute(−1)) and CYP3A4/5 (midazolam 1′-hydroxylation; K(I) = 14.8 μM, k(inact) = 0.019 minute(−1)); (−)-β-hydrastine inhibited CYP2C9 (diclofenac 4′-hydroxylation; K(I) = 49 μM, k(inact) = 0.036 minute(−1)), CYP2D6 (K(I) > 250 μM, k(inact) > 0.06 minute(−1)), and CYP3A4/5 (K(I) = 28 μM, k(inact) = 0.056 minute(−1)); and hydrastinine inhibited CYP2D6 (K(I) = 37 μM, k(inact) = 0.049 minute(−1)) activity. Berberine additionally exhibited allosteric effects on midazolam hydroxylation, showing both positive and negative heterotropic cooperativity. Experiments with recombinant isozymes showed that berberine activated midazolam 1′-hydroxylation by CYP3A5, lowering K(m(app)), but showed mixed inhibition and negative cooperativity toward this reaction when catalyzed by CYP3A4. Berberine inactivated CYP3A4 at a much faster rate than CYP3A5 and was a noncompetitive inhibitor of midazolam 4-hydroxylation by CYP3A4 but a strong mixed inhibitor of the CYP3A5 catalyzed reaction. These complex kinetics should be considered when extrapolating the risk for NP-drug interactions involving goldenseal. SIGNIFICANCE STATEMENT: Robust kinetic parameters were determined for the reversible and time-dependent inhibition of CYP2C9, CYP2D6, and CYP3A4/5 activities in human liver microsomes by major component isoquinoline alkaloids contained in the botanical natural product goldenseal. The alkaloid berberine also exhibited opposing, isozyme-specific allosteric effects on midazolam hydroxylation mediated by recombinant CYP3A4 (inhibition) and CYP3A5 (activation). These data will inform the development of a physiologically based pharmacokinetic model that can be used to predict potential clinically relevant goldenseal-drug interactions.